Kepemimpinan Transformasional di Era 4.0 dalam Upaya Meningkatkan Manajemen Kinerja Organisasi - Anggraeni, Devi; Quintaniaa, Melani; Budhi Pratomo, Wisnu (Jurnal Ilmu Manajemen, 2024)
The leadership model in organizations is still entangled in negative stereotypes. No wonder then if the names of new leaders appear with a non-mainstream style. This is certainly one indicator that the old-style leadership model is still dominant in the bureaucracy. The stereotype of the old style of leadership in the bureaucracy is like placing the leader as a father and subordinate as a child who always has to obey every command. The concept of transformational leadership is an art that must be practiced by all leaders in every organization, because a transformational leader will prioritize communication in interacting with all elements he leads and can directly optimize the performance management of an organization through his communication skills.